Contribution and Analysis of Economic Base in the Agricultural Sector in Tomohon City: Kontribusi Dan Analisis Basis Ekonomi Pada Sektor Pertanian Di Kota Tomohon - Merlin Wilhelmina Singkoh; Fadly Steven Jefry Rumondor; Daniel Stefanus Imanuel Sondakh (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to determine whether the agricultural sector is a basic or non-basic sector that can drive the economic development of Tomohon City. This research was conducted in Tomohon City. The writing time lasted for 3 months from March to June 2024. The type of data used is time series data, namely GRDP at constant prices for Tomohon City from 2018-2023 and GRDP of North Sulawesi Province in 2018-2023. The analysis used is contribution analysis (Share Analysis), location quotient (LQ) analysis. The results of the study show that the agricultural sector contributes to the economic development of Tomohon City. The average contribution of the agricultural sector/year is 13.34%. The agricultural sector is a non-basic sector in Tomohon City. Horticulture, food crops and plantation crops have a role in improving the regional economy